Systematic investigation of the relationships of trimethylamine N-oxide and l-carnitine with obesity in both humans and rodents. Issue 9 (11th September 2020) - Gao, Xiang; Sun, Guang; Randell, Edward; Tian, Yuan; Zhou, Haicheng
Abstract : In this study, we systematically investigated the relationships of trimethylamine N -oxide (TMAO) and l -carnitine with obesity in both humans and mice. Abstract : Previous studies suggested the potential associations of trimethylamine N -oxide (TMAO) and its metabolic precursor l -carnitine with obesity. However, existing evidence is limited and inconsistent. In the present study, we perform a cross-sectional analysis of the associations of serum levels of TMAO and l -carnitine with obesity measures, including BMI, body fat distribution and body composition in 1081 participants from the general Newfoundland population. The dietary effects of TMAO and l -carnitine in preventing high fat diet-induced obesity in both male and female mice were also evaluated. We found significant associations between higher serum l -carnitine levels and obesity (higher BMI, body fat mass and VT%) in women, but not in men after controlling multiple confounding factors. Serum TMAO levels were positively associated with age, but not obesity in both men and women. Dietary TMAO had no influence on fat accumulation in high fat diet-fed mice. However, l -carnitine supplementation prevented high fat diet-fed induced obesity in both male and female mice by up-regulating lipolysis and down-regulating lipogenesis in white adipose tissues. The present study provides further evidence for the relationships between TMAO, l -carnitine and obesity.